PRESERVATION BY SOCIALIZING THE BENEFITS AND NUTRITIONAL CONTENT OF SIMALUNGUN TYPICAL SAUCES TO WOMEN™S ORGANIZATION OF SIMALUNGUN CENTRAL BUREAU OF STATISTICS - Damanik, Marini (Universitas Negeri Medan, 2022)
Preservation of Simalungun's typical sauce to the women™s organization of Simalungun Central Bureau of Statistics by the Medan State University Research and Service Center, namely tinuktuk sauce, have been carried out by socializing the benefits and contents of which have been carried out online. Preserving this tinuktuk sauce as a form of community service has already been done by the Universita Negeri Medan community research and service center. It is implemented by socializing the benefits and nutritional content of tinuktuk. In the webinar, not only the introduction of the Simalungun tinuktuk sauce, but also the nutritional content and benefits of the tinuktuk sauce were also socialized. This is also related to the importance of nutritional needs to increase body immunity during the COVID-19 period. In the process of socializing efforts to preserve the benefits and nutritional content of Simalungun's special sauce, there was a significant difference in result between the pre-test and post-test, namely in the pre-test 43% and post-test 84%, and this indicates that participants know the benefits and nutritional content of Simalungun™s typical tinuktuk sauce. This community service activity went smoothly because the participant already knew about the nutritional content and benefits of Simalungun™s typical tinuktuk sauce and it™s hoped that the tinuktuk sauce can be preserved.